Structural analysis of Eu3+ in Li2O-MO-B2O3-Eu2O3(M=Mg, Ca, Sr, Ba) glass using XANES and EXAFS. (March 2023) - Rajaramakrishna, R.; Damdee, B.; Kirdsiri, K.; Saiyasombat, C.; Kidkhunthod, P.; Kothan, S.; Kaewkhao, J.
Abstract: The research focuses on the structural changes, coordination and interatomic distance of Europium doped Li2 O-MO-B2 O3 (M = Mg, Sr) glasses. The detailed analysis was subjected to understand Eu 3+ ions in lithium magnesium borate and lithium strontium borate glasses as determined by the extended X-ray absorption fine structure analysis. XANES spectra of Eu2 O3 content doped in the present glasses showed Eu 3+ state upon the x-ray as incident source. The metal LIII edges, and K edges are investigated concerning alkaline earth ion glasses and their interactions with local environment. In this work, europium and barium ions in lithium borate glasses are studied by L III -edges, strontium and calcium ions in lithium borate glasses are studied by K- edges using X-ray absorption spectroscopy to reveal the relationship between alkali earth metal ions with Eu 3+, Ba 2+, Ca 2+, and Sr 2+ ion local structure. The nearest neighbors of Eu for the first shell were analyzed for Eu–O distance in Eu 3+ -doped glasses by EXAFS analysis and found to be in the range of 2.35–2.36 Å. Judd-Ofelt analyses were performed, and JO parameters showed Ω4 > Ω2 > Ω6 trend for Mg, Ca, Sr in lithium borate glasses while a Ω2 > Ω4 > Ω6 trend for Ba in lithium borate glasses. Radiative properties were analyzed using JO parameters to calculate stimulated emission cross-section, branching ratio, and radiative lifetime. The calculation was also taken care of with thermal correction and found that the data obtained after thermal correction shows higher values. Highlights: Li2 O-MO-B2 O3 (M = Mg, Sr) glasses were synthesized by melt quench technique. Judd-Ofelt analysis was performed and found the trend Ω4 > Ω2 > Ω6 . Radiative properties were analyzed using JO parameters. Sr K-edge, Barium L III – edge, Calcium K-edge were investigated using XANES. EXAFS analysis with first three shells for Eu 3+ ions doped in Li2 O-MO-B2 O3 (M = Mg, Ca, Sr, Ba) glasses evaluated.